Gender and cultural differences in self-deception - Che Roslan, Che Nurul Herdawatti; Mohamad Kadari, Haire; Ninam Shah, Mohd Firdaus; Roslan, Nurul Nadia; Mohd Mahudin, Nor Diana (2014)
The extent to which gender and cultural background interact to influence self-deception was investigated. Four African (Male = 2; Female = 2) and four Malaysian university students (Male = 2; Female = 2) were instructed to submerge their arms and hands in cold water before and after physical exercise. Depending on experimental condition, participants were informed that a long life expectancy corresponded with either an increase or decrease of tolerance to cold water after the exercise. Results show that participants changed the amount of time they held their arms underwater on the second trial when they were confronted with deliberate misrepresentation of a rising, healthy life expectancy. However, analysis of variance (ANOVA) results reveal that neither significant difference between males and females (F (3, 4) = 0.553, p= 0.673) nor between cultures (F (3, 4) = 0.786, p= 0.561) were found in the tendency to self-deceive. Although these findings are not in accordance with the research hypotheses, they may be hypothesis-generating and suggest the potential role of gender and cultural factors in varying self-deceptive behaviour. Further research with a larger sample size and better experimental procedures is warranted to continue to investigate the potential role of these factors.